The activity of Muslim women in the literature of the era of early Islam - L.A. Mason Jassim Abdullah; Miss. Habiba Mustafa Rashid; L.A. Hawneaz Mustafa Rashid; L.A. Hosnia Jassim Abdullah (Genius Journals, 2023)
This research examines models of the presence of Muslim women and their role in literary arts during the early Islamic period. They were influenced by the qualitative leap that literature witnessed under Islam, and this was reflected in their literary activity. They excelled in the fields of poetry and prose, and their literary presence stood out through their poetry and prose arts, including oratory, books, and letters.
Keywords: Muslim women; the era of early Islam; poetry